Protective discrimination: why Scheduled Tribes lag behind Scheduled Castes - Xaxa, Virginius (2001)
The pattern of historical development has been different for the scheduled castes and scheduled tribes with the latter never having been an integral part of mainstream society. How effective has been the policy of protective discrimination in removing the disabilities suffered by the scheduled tribes? This paper attempts a comparison between the relative benefits to the scheduled tribes and scheduled castes as a result of the policy of protective discrimination. Following upon this, the author examines why one category has fared beter than the other. - Reproduced
Keywords: Discrimination - India; Scheduled Tribes; Scheduled Castes; Backward classes - India; Backward classes